Infertility treatment for Chinese women with P450 oxidoreductase deficiency: Prospect on clinical management from IVF to FET - Li, Yan; Zhang, Cui-Lian; Zhang, Shao-Di (Frontiers in Endocrinology, 2022)
Cytochrome P450 oxidoreductase deficiency (PORD) is a rare recessive disease with multiple clinical manifestations, which is usually diagnosed in neonates and children because of the ambiguous genitalia or skeletal malformations. Besides, the paucity of studies do not allow us to establish whether adult-onset PORD is associated with infertility. Here we report clinical and laboratory findings in two phenotypically normal women diagnosed as PORD who undergone the procedure of in vitro fertilization (IVF) and frozen embryo transfer (FET). We modified the gonadotropins stimulation protocol during controlled ovarian stimulation (COH) and suggest the use of 17β-estradiol via vaginal route for uterus endometrium preparation in hormone replacement therapy (HRT) cycles. We presume that PORD may be associated with infertility in several aspects, including the disordered steroidogenesis, endometrium impairment, attenuation of drug metabolism and high risk of miscarriage. Our observations will help the early diagnosis and make a tailored approach of infertility management in adult-onset PORD.